2020
DOI: 10.1093/ajhp/zxaa310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacist input on HIV management may improve antiretroviral prescribing for psychiatric patients

Abstract: Purpose The results of a study to determine the difference in HIV management with clinical pharmacist input in an adult psychiatric hospitalized patient population are reported. Methods Single-center, retrospective study of patients admitted to a psychiatric hospital on antiretroviral (ARV) medication(s) from October 2016 to March 2017 (phase I: no pharmacist involvement), October 2017 to March 2018 (phase II: partial pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“… 5 However, multiple studies have demonstrated that alternatives to the classic medicine-centered design were more effective in increasing patients’ adherence or improving associated health outcomes. 6 , 7 Patient demographic, educational and cognitive factors, as well as the use of health resources should be previously evaluated in order to provide the best care for patients. Moreover, enhancing the empowerment of the patients should be also considered a priority intervention to increase their self-efficacy for medication management.…”
Section: Introductionmentioning
confidence: 99%
“… 5 However, multiple studies have demonstrated that alternatives to the classic medicine-centered design were more effective in increasing patients’ adherence or improving associated health outcomes. 6 , 7 Patient demographic, educational and cognitive factors, as well as the use of health resources should be previously evaluated in order to provide the best care for patients. Moreover, enhancing the empowerment of the patients should be also considered a priority intervention to increase their self-efficacy for medication management.…”
Section: Introductionmentioning
confidence: 99%